2002
DOI: 10.1016/s0896-6273(02)00799-7
|View full text |Cite
|
Sign up to set email alerts
|

EphB Forward Signaling Controls Directional Branch Extension and Arborization Required for Dorsal-Ventral Retinotopic Mapping

Abstract: We report that EphB receptors direct unique axonal behaviors required for mapping the dorsal-ventral (D-V) retinal axis along the lateral-medial (L-M) axis of the superior colliculus (SC). EphBs are expressed in a D-V gradient, ephrin-B1 in a L-M gradient in SC, and ephrin-B3 at its midline. EphBs and ephrin-Bs are expressed in countergradients in retina and SC. Developmental analyses reveal that retinal axons lack D-V ordering along the L-M axis, but directionally extend branches along it to establish ordered… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

23
326
2

Year Published

2004
2004
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 281 publications
(351 citation statements)
references
References 49 publications
23
326
2
Order By: Relevance
“…In such a case, the primary axons of ND RGCs might terminate in the appropriate zone, preserving nearest-neighbor connectivity, but additional interstitial branches would be misguided and form multiple anteriorly shifted ectopic TZs. A similar mechanism has been demonstrated in the EphB2/EphB3 double mutant where RGC axons extend interstitial branches beyond the primary TZ location, in addition to a TZ in the correct location (Hindges et al, 2002). However, the failure to demonstrate multiple TZs in mutant and control SCs retrogradely labeled in the posteriallateral region suggests an alternative mechanism for ectopic TZs in Phr1 retinal mutants.…”
Section: Discussionsupporting
confidence: 58%
“…In such a case, the primary axons of ND RGCs might terminate in the appropriate zone, preserving nearest-neighbor connectivity, but additional interstitial branches would be misguided and form multiple anteriorly shifted ectopic TZs. A similar mechanism has been demonstrated in the EphB2/EphB3 double mutant where RGC axons extend interstitial branches beyond the primary TZ location, in addition to a TZ in the correct location (Hindges et al, 2002). However, the failure to demonstrate multiple TZs in mutant and control SCs retrogradely labeled in the posteriallateral region suggests an alternative mechanism for ectopic TZs in Phr1 retinal mutants.…”
Section: Discussionsupporting
confidence: 58%
“…He proposed that the retina and the tectum have a system of complementary chemical cues that help map the innervating axons onto their appropriate locations in the tectum (Sperry 1963). Subsequent work by many groups has shown that retinal axons compete amongst themselves in an activity dependent manner for tectal territory, and can thereby redistribute themselves within the target, but the basic finding that retinal axons initially prefer to grow to or branch in specific target locations has been vindicated by the discovery that counter gradients of Ephs and ephrins help establish retinotopy in visual centers (Cheng et al 1995;Feldheim et al 2000;Hindges et al 2002;McLaughlin et al 2003) (see Feldheim and O'Leary 2010). …”
Section: Axons Extend In Vivo In a Directed Mannermentioning
confidence: 99%
“…However, even surface localized guidance cues can be used to generate a gradient of guidance information. For example, gradients of ephrin expression in the tectum and superior colliculus help organize the retinotopic projections of retinal ganglion cells onto their target fields (Cheng et al 1995;Feldheim et al 2000;Hindges et al 2002;McLaughlin et al 2003;O'Leary 2010).…”
Section: Tropic Guidance Cuesmentioning
confidence: 99%
“…Factors that have been shown to shape axonal arbor growth include not only extracellular guidance cues (Yates et al, 2001;Hindges et al, 2002) but also synaptic activity (O'Rourke et al, 1994;Debski and Cline, 2002;Ruthazer and Cline, 2004) and intracellular and intercellular signaling (Hall et al, 2000;CohenCory and Lom, 2004;Govek et al, 2005). Similarly, progress has been made in elucidating the molecular mechanisms by which synapses are assembled (Goda and Davis, 2003;Li and Sheng, 2003;Ziv and Garner, 2004).…”
Section: Introductionmentioning
confidence: 99%